THE INTERPRETATION OF EASTERN MORAL VALUES IN “RABIʼ AL-ABROR” (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the issues of Eastern morality reflected in MahmudZamakhshari’s “Rabiʼ al-abror wa nusus al-akhyor.” The work describes noble ideassuch as human virtues, etiquette, morality, knowledge and enlightenment, honesty,generosity, modesty, patience, and contentment through the wisdom and narrations ofEastern thinkers. The analysis draws on selected passages from the work to examineits philosophical methodology, its integration of Islamic and pre-Islamic sources, andits treatment of knowledge, truth, and moral responsibility as the foundations of humanperfection.
Keywords: Zamakhshari; Eastern morality; virtue; knowledge; honesty; deontological ethics; Islamic philosophy; wisdom literature; moral education.